2018
DOI: 10.3892/etm.2018.6426
|View full text |Cite
|
Sign up to set email alerts
|

Lycium�barbarum polysaccharides attenuates the apoptosis of hippocampal neurons induced by sevoflurane

Abstract: Following the application of inhalational anesthetics, including sevoflurane, patients may suffer from neural injury. The present study was conducted to explore the mechanism involved in Lycium barbarum polysaccharides (LBP) treatment of sevoflurane injured hippocampal neurons. Primary hippocampal neurons were isolated from Sprague Dawley embryonic rats. The Cell Counting Kit-8 (CCK-8) assay was used to detect cell viability. Furthermore, flow cytometry (FCM) was used to determine cell proliferation and apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…However, 3% sevoflurane is quite high and this level is rarely used in clinical practice, which is a limitation of the present study. MTT and FCM analysis were carried out to measure the effects of 3% sevoflurane on neuronal cell growth and apoptosis at 0, 2, 4, and 6 h. Consistent with a previous study [20], we found that 3% sevoflurane inhibited neuronal cell viability and promoted cell apoptosis in a time-dependent manner, so we chose to treat neuronal cells with 3% sevoflurane for 6 h in subsequent experiments. Abnormal apoptosis can also suppress cell growth, and sevoflurane neurotoxicity is associated with increased apoptosis, such as abnormal regulation of Bcl-2 family members and caspases [25,26].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…However, 3% sevoflurane is quite high and this level is rarely used in clinical practice, which is a limitation of the present study. MTT and FCM analysis were carried out to measure the effects of 3% sevoflurane on neuronal cell growth and apoptosis at 0, 2, 4, and 6 h. Consistent with a previous study [20], we found that 3% sevoflurane inhibited neuronal cell viability and promoted cell apoptosis in a time-dependent manner, so we chose to treat neuronal cells with 3% sevoflurane for 6 h in subsequent experiments. Abnormal apoptosis can also suppress cell growth, and sevoflurane neurotoxicity is associated with increased apoptosis, such as abnormal regulation of Bcl-2 family members and caspases [25,26].…”
Section: Discussionsupporting
confidence: 69%
“…In this study, we separated hippocampal neurons from Sprague-Dawley embryonic rats, and used 3% sevoflurane to induce a neuronal cell injury model [20]. We used 3% sevoflurane to stimulate the nerve injury, as previously described [20]. However, 3% sevoflurane is quite high and this level is rarely used in clinical practice, which is a limitation of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sevo urane is an inhalational anesthetics, which is commonly used in cesarean delivery and pediatric clinical application [2]. Previous evidence has suggested that sevo urane exposure has certain harm on learning and cognitive functions, especially for children [5,11].…”
Section: Discussionmentioning
confidence: 99%
“…Sevo urane is one of the most comment used inhalational anesthetics, which is characterized by rapid induction and recovery properities [1]. It is widely used in cesarean delivery and pediatric clinical application [2]. Sevo urane has some neurotoxicity for the nervous system, especially for developing brain [3][4][5].…”
Section: Introductionmentioning
confidence: 99%